Long-term results of endoscopic resection in early gastric cancer: The western experience - Manner, Hendrik; Rabenstein, Thomas; May, Andrea; Pech, Oliver; Gossner, Liebwin; Werk, Daniel; Manner, Nicola; Günter, Erwin; Pohl, Jürgen; Vieth, Michael; Stolte, Manfred; Ell, Christian (American Journal of Gastroenterology, 2009)
OBJECTIVES: In the West, neither acute nor long-term results of endoscopic resection (ER) for early gastric cancer (EGC) have been reported in large studies. The aim of this study was to prospectively evaluate the efficacy and safety of ER in patients with EGC in a long-term follow-up (FU). METHODS: From May 1995 to October 2004, 179 patients were referred to our department for endoscopic therapy (ET) of gastric cancer (GC). Of these, 43 patients had intramucosal GC with a diameter of up to 30 mm and underwent ER with curative intent. All patients underwent a strict FU protocol at regular intervals. RESULTS: Of the 43 patients, 42 fulfilled our low-risk criteria for ET of EGC: gross tumor type I/II, intramucosal GC, diameter up to 30 mm, tumor differentiation G1/G2, and no infiltration into lymph vessels/veins. Two patients were not available for FU (remission status not evaluated). In another patient, gastric mucosa-associated lymphoid tissue lymphoma was detected simultaneously, and he was referred for surgery. 38 (97%) of the remaining 39 patients who underwent definitive ET (23 males (59%); mean age 69±10 years) achieved complete remission (CR) after a mean of 1.3±0.6 ER sessions. Minor complications (not Hb-relevant bleeding) occurred in 7 of the 39 patients (18%) and major complications (5 Hb-relevant bleeds, 1 covered perforation; all managed conservatively) in 6 patients (15%). During FUs (mean 57 months; range 5-137), recurrent or metachronous lesions were observed in 11 patients (29%). All lesions were successfully treated by repeated ET. No tumor-related deaths occurred during FU. CONCLUSIONS: Although ER for EGC in Western countries is effective, it is associated with a relevant risk of complications. In view of the possibility of recurrent or metachronous neoplasia, a strict FU protocol is mandatory. © 2009 by the American College of Gastroenterology.
CRIS-Team Scopus Importer:2025-03-05